LEGAL RESPONSIBILITY FOR VIOLATIONS OF LEGISLATION ON SUBSOIL PROTECTION - Zhussipova, Bakyt; Kaskeeva, A. (E-Journal VFU, 2024)
This article addresses the theoretical aspects of legal frameworks for environmental protection and ensuring environmental safety in subsoil use. By analyzing existing legislation, the theoretical characteristics of environmental protection in subsoil useare identified
Keywords: subsoil use; environmental protection; liability for violation of legislation on subsoil protection